Archive in/aus Literatur Wechselspiele zweier Medien - Neuhuber, Christian; Kastberger, Klaus (Literatur und Archiv, 2021)
Literary estates as media formations make knowledge of archives indispensable. Do creative people already view their workshops as future archives? What kinds of interplay is there between archives and literature? And what is the basis for genres such as the archive novel, the blog novel, and docufiction? The contributions by renowned cultural studies scholars in this volume use examples to show how literature and archives encounter one another.